2022
DOI: 10.26877/bioma.v11i2.11533
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of glucomannans and anthocyanins combination in the containing microparticle protein on fat digestibility and fat deposition on broiler chicken

Abstract: This study aims to evaluate the effects of combination of glucomannan and anthocyanin in feeds containing protein microparticles on fat digestibility and fat deposition in broiler chickens. The 216 healthy 7-day-old broiler chicks strain CP 707 was used with treatment of glucomannan from porang tuber extract and anthocyanins from purple sweet potato extract. The study was arranged by a completely randomized design (CRD) with a factorial pattern with treatment consisting of 2 factors (A and B). In A, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The third day ration contained an indicator, while the fourth day ration did not. Every day, excreta were collected by spraying 0.2 N HCL every 2 hours (Krismiyanto et al, 2022). The excreta was dried and crushed before being analyzed for crude protein content using the Kjeldahl method.…”
Section: Protein Digestibilitymentioning
confidence: 99%
“…The third day ration contained an indicator, while the fourth day ration did not. Every day, excreta were collected by spraying 0.2 N HCL every 2 hours (Krismiyanto et al, 2022). The excreta was dried and crushed before being analyzed for crude protein content using the Kjeldahl method.…”
Section: Protein Digestibilitymentioning
confidence: 99%
“…namely at P1 3.7x106 CFU/g and P2 4.4x106 CFU/g. (25) stated that an increase in lactic acid bacteria produced lactic acid and Short Chain Fatty Acid production. The increase in SCFA and lactic acid accompanied by decreased pH of the digesta will further reduce pH in the cecum.…”
Section: Effect Of Treatment On Crude Fiber Digestibilitymentioning
confidence: 99%
“…Lactic acid bacteria and other nonpathogenic bacteria that produce organic acids, especially lactic acid, can reduce pH in the cecum (19). On other hands, (25) added that the increasing population of lactic acid bacteria in the caecum would help break down carbohydrates, which can then be fermented by cellulolytic bacteria. Related to this results, (15) reported that the population of cellulolytic bacteria in the digestive tract of poultry was 63x107 cfu/g, where the bacteria could degrade crude fiber.…”
Section: Effect Of Treatment On Crude Fiber Digestibilitymentioning
confidence: 99%
See 1 more Smart Citation